A Novel Head Capsule Labial Gland Lobe in the Black Field Cricket (Orthoptera: Gryllidae). Issue 4 (22nd July 2020) - Pereira, Monique Campos; Cooper, Paul D
Abstract: We describe a pair of labial gland lobes on either side of the retrocerebral complex in the head of the Australian black field cricket, Teleogryllus commodus Walker. As the retrocerebral complex includes the corpora cardiaca and corpora allata, hormones secreted by these glands can be absorbed by these lobes. These lobes of the labial gland are connected to the thoracic lobes via a relatively long duct that enters the main duct draining the thoracic lobes. Measurement of the flow rate of dye from head to thorax in the ducts is rapid, suggesting that these glands may serve as a transport system into the thoracic region. Both serotonin and adipokinetic hormone are shown to be present in the lobes near the retrocerebral complex and the ducts of the thoracic lobes, but whether this connection between the head and thorax acts as a hormone transporter is still unclear. Graphical Abstract: